1993
DOI: 10.1111/j.1349-7006.1993.tb02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Glandular Stomach Cancers in C3H Mice Treated with N‐Methyl‐N‐nitrosourea in the Drinking Water

Abstract: Establishment of an animal model of stomach carcinogenesis in mice was attempted using N‐methyl‐N‐nitrosourea (MNU) in the drinking water. One hundred and forty‐eight male 6‐week‐old C3H mice were given MNU in their drinking water at a concentration of 120 ppm (group 1), 60 ppm (group 2), 30 ppm (group 3) or 0 ppm (group 4) for 30 weeks. At the end of this time, dose‐related induction of adenomatous hyperplasias was found. From weeks 31 to 54 adenocarcinomas developed in a dose‐dependent manner in groups 1, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…23,24) Therefore, the establishment by Tatematsu et al of a mouse experimental gastric cancer model using MNU to yield both differentiated and undifferentiated type carcinomas was important. 11,12) In the present study undifferentiated type carcinomas were similarly induced, being positively linked to high concentrations of MNU. It has been suggested that differentiated and undifferentiated types of gastric carcinomas in man may develop through different genetic pathways.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…23,24) Therefore, the establishment by Tatematsu et al of a mouse experimental gastric cancer model using MNU to yield both differentiated and undifferentiated type carcinomas was important. 11,12) In the present study undifferentiated type carcinomas were similarly induced, being positively linked to high concentrations of MNU. It has been suggested that differentiated and undifferentiated types of gastric carcinomas in man may develop through different genetic pathways.…”
Section: Discussionmentioning
confidence: 67%
“…However in a recently established mouse experimental gastric cancer model using MNU the types of tumors proved more similar to human gastric cancers in terms of their histopathological features than those typically found in rats. 11,12) The present study was performed to assess the effects of carcinogen concentration on the histopathological type and incidence of gastric carcinomas induced in our mouse model. For this purpose MNU was given at different concentrations for different periods so that all groups would receive the same total quantity of carcinogen, in theory.…”
mentioning
confidence: 99%
“…Gastric cancers were induced in C3H mice by providing N-methyl-N-nitrosourea (MNU) in drinking water (Tatematsu et al, 1993), and four cell lines derived from these mouse glandular stomach carcinomas were isolated (Ichinose et al, 1998). In this study, we found that these mouse gastric cancer cells exhibit properties remarkably similar to those of human gastric cancer cells.…”
mentioning
confidence: 60%
“…To examine the role of ASK1 in GC, we used a mouse model of chem-ically induced gastric tumorigenesis. As the administration of N-methyl-N-nitrosourea (MNU) results in efficient gastric tumor induction in mice (14), wild-type (WT) and ASK1 −/− mice were administered MNU as described previously ( Fig. 2A).…”
Section: Increased Expression Of Ask1 In Human Gastricmentioning
confidence: 99%